2017
DOI: 10.1097/ta.0000000000001578
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intimate partner homicide in Illinois, 2005–2010: Findings from the Illinois Violent Death Reporting System

Abstract: Epidemiologic, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
2
1
2
Order By: Relevance
“…The current study also found that compared with non-IPV-related homicides, IPV-related homicides post-release were significantly more likely to be caused by means other than the use of a firearm (i.e., blunt trauma to head/body, stabbing, or strangulation). This finding is counter to prior research identifying IPV perpetrators’ access to firearms as an important risk factor for IPH (Campbell et al, 2003), as well as research suggesting that many IPHs involve the use of firearms (Cooper & Smith, 2011; Federal Bureau of Investigation, U.S. Department of Justice, 2015; Puzone, Saltzman, Kresnow, Thompson, & Mercy, 2000; Yousuf et al, 2017). Given this study’s unique focus on homicides post-release from jail or prison, it is possible that policies limiting access to firearms because of felonies, misdemeanor domestic violence (DV) crimes, other violent misdemeanor crimes, or restraining order prohibitions contributed to greater use of homicide means other than firearms among the IPV-related homicides.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The current study also found that compared with non-IPV-related homicides, IPV-related homicides post-release were significantly more likely to be caused by means other than the use of a firearm (i.e., blunt trauma to head/body, stabbing, or strangulation). This finding is counter to prior research identifying IPV perpetrators’ access to firearms as an important risk factor for IPH (Campbell et al, 2003), as well as research suggesting that many IPHs involve the use of firearms (Cooper & Smith, 2011; Federal Bureau of Investigation, U.S. Department of Justice, 2015; Puzone, Saltzman, Kresnow, Thompson, & Mercy, 2000; Yousuf et al, 2017). Given this study’s unique focus on homicides post-release from jail or prison, it is possible that policies limiting access to firearms because of felonies, misdemeanor domestic violence (DV) crimes, other violent misdemeanor crimes, or restraining order prohibitions contributed to greater use of homicide means other than firearms among the IPV-related homicides.…”
Section: Discussioncontrasting
confidence: 87%
“…Quantitative and qualitative results indicated additional circumstantial factors of IPV-related post-release homicides consistent with the IPH literature, including (a) homicide location (i.e., homicide occurring in the home, which was typically shared by both the homicide victim and homicide perpetrator; Yousuf et al, 2017) and (b) presence of substance use prior to the homicide incident (e.g., Aldridge & Browne, 2003; Campbell et al, 2007). The current study found that many of the homicide victims and perpetrators used substances prior to the incident and about half of the homicide victims had histories of substance use/abuse.…”
Section: Discussionsupporting
confidence: 64%
“…Um estudo sobre fatores associados ao homicídio por parceiro íntimo evidenciou que, nos casos nos quais o perpetrador tinha histórico de agressões, as vítimas foram 2,4 vezes mais propensas a sofrer a lesão fatal na sua residência. Igualmente, nos casos em que o autor era o atual parceiro da vítima, houve duas vezes mais chances de a lesão que ocasionou o óbito ocorrer na residência da vítima (18) . Na maioria das vezes, as vítimas estavam envolvidas em um episódio de agressão física ou verbal com um parceiro íntimo quando o homicídio aconteceu (18) .…”
Section: Discussionunclassified
“…Igualmente, nos casos em que o autor era o atual parceiro da vítima, houve duas vezes mais chances de a lesão que ocasionou o óbito ocorrer na residência da vítima (18) . Na maioria das vezes, as vítimas estavam envolvidas em um episódio de agressão física ou verbal com um parceiro íntimo quando o homicídio aconteceu (18) .…”
Section: Discussionunclassified
“…Estimates indicate that if an intimate partner homicide is committed with a firearm, the offender is twice as likely to kill multiple victims than if the offender used a different weapon (Smucker et al., ). Multiple victim intimate partner homicides are not uncommon: In 6% to 20% of events in which an individual kills his or her intimate partner, that individual also kills at least one other person, most commonly a child or other family member (Smith et al., ; Smucker et al., ; Yousuf et al., ). In a small percentage of these events, the violent intimate partner fatally shoots at least four people, making the homicide a mass shooting.…”
Section: Literature Reviewmentioning
confidence: 99%